Flipped classroom based on objective structured clinical examinations analysis by undergraduate students of Pharmacology course from the Podiatry Degree improve their learning and assessment communication skills about medicines - Bellido-Estévez, Inmaculada; Blanco-Reina, Encarnación; Bellido Estévez, María Victoria; García-Arnés, Juan Antonio; Gómez-Luque, José Aurelio (My University, 2019)
We aim to evaluate the impact of the individual and in-group analysis of OSCEs (filmed by other students) looking for correct and incorrect behaviours and contents in their learning of pharmacology. Summary of work and outcomes: A 5-year prospective study in which students of Pharmacology course from the Podiatry Degree analysed filmed OSCEs individually and in a group in a flipped classroom. Each group (max 5 students) analysed along 1 week a filmed OSCE, prepare a summary of correct and incorrect items related to clinical events, medicines uses, and people behaviours. The students presented their analysis results to the rest of the class. After each presentation, the other students of the class were encouraged to ask questions and after that, the students voluntarily answered a satisfaction survey. Result and Discussion: 405 students, 65.2% female, 20±5.3 years old were included. Students spend 13.4±5.4 h on making the filmed-OSCE analysis. The percentage of students satisfied with this way of studying pharmacology was 96.5%. OSCEs analysis by students increased their percentage of success in the final assessment in both OSCEs-related and OSCEs-non-related questions (+18.5% and +10.1%). Conclusion: Filmed Objective Structured Clinical Examinations analysis by undergraduate students on the Pharmacology course of Podiatry Degree improved their knowledge about medicines use and their communication skills during the assessment.
Comunicación cartel con defensa oral
Keywords: Farmacología; Flipped classroom; Objective structured clinical examination; Assessment; Communication skills